Pál Maliga, founder of the research in floral biology of fruit species in Hungary - Nyéki, J.; Soltész, M. (International Journal of Horticultural Science, 2003)
Pál Maliga founded the Hungarian research in floral biology of fruit species during his more than forty-year-long carrier. Almost all pome and stone fruit species have been covered by his activities, but he also dealt with the fertility of walnut and chestnut. Regularities have been revealed and the methodical studies opened the way to approach and elaborate alternatives for the association of varieties in planning high yielding commercial plantations. In his breeding activity the choice of crossing parental varieties was based on the knowledge in fertility relations. The obtained sour cherry varieties represent the world-wide maximum quality, reliability and security of yields. Hungarian renewed sour cherry cultivation owes its fame and prosperity to those varieties, nevertheless also to the radical knowledge of the biological bases of fertility.